Evaluation of TP53 and IGHV clinical molecular prognostic testing for patients with Chronic Lymphocytic Leukaemia at Tygerberg Hospital - Nkwanyane, Tinashe Nthabiseng (Stellenbosch : Stellenbosch University, 2026)
Thesis (M in Pathology)--Stellenbosch University, 2026.